Primary Episodic Ataxias - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The clinical and genetic diagnosis, genotype-phenotype correlations, pathophysiology and treatment of primary episodic ataxia syndromes are reviewed by researchers from Departments of Neurology, UCLA School of Medicine, Los Angeles, CA; National Hospital for Neurology, Queen Square, London, UK; Johns Hopkins University School of Medicine, Baltimore, MD; and University of Rochester School of Medicine, NY, USA.